Extracts of Fruits and Vegetables Activate the Antioxidant Response Element in IMR-32 Cells. Issue 9 (29th July 2015) - Orena, Stephen; Owen, Jennifer; Jin, Fuxia; Fabian, Morgan; Gillitt, Nicholas D; Zeisel, Steven H
Abstract: Background: The biological effects of antioxidant nutrients are mediated in part by activation of antioxidant response elements (AREs) on genes for enzymes involved in endogenous pathways that prevent free radical damage. Traditional approaches for identifying antioxidant molecules in foods, such as total phenolic compound (TP) content or oxygen radical absorption capacity (ORAC), do not measure capacity to activate AREs. Objectives: The goal of this study was to develop an assay to assess the ARE activation capacity of fruit and vegetable extracts and determine whether such capacity was predicted by TP content and/or ORAC activity. Methods: Fruits and vegetables were homogenized, extracted with acidified ethanol, lyophilized, and resuspended in growth medium. Human IMR-32 neuroblastoma cells, transfected with an ARE-firefly luciferase reporter, were exposed to extracts for 5 h. Firefly luciferase was normalized to constitutively expressed Renilla luciferase with tertiary butylhydroquinone (tBHQ) as a positive control. TP content and ORAC activity were measured for each extract. Relations between TPs and ORAC and ARE activity were determined. Results: A total of 107 of 134 extracts tested significantly activated the ARE-luciferase reporter from 1.2- to 58-fold above that of the solvent control ( P < 0.05) in human IMR-32 cells. ARE activity, TP content, and ORAC ranked higher in peels than in associated flesh. Despite this relation, ARE activity did not correlate with TP content (Spearman ρ = 0.05, P = 0.57) and only modestly but negatively correlated with ORAC (Spearman ρ = −0.24, P < 0.01). Many extracts activated the ARE more than predicted by the TP content or ORAC. Conclusions: The ARE reporter assay identified many active fruit and vegetable extracts in human IMR-32 cells. There are components of fruits and vegetables that activate the ARE but are not phenolic compounds and are low in ORAC. The ARE-luciferase reporter assay is likely a better predictor of the antioxidant benefits of fruits and vegetables than TP or ORAC.